Regulacje prawne postępowania antydumpingowego w Polsce w świetle przystąpienia do Unii Europejskiej - Jorasz, Alicja (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2004)
Passing of the Law of December 11, 1997 on protection of the Polish customs zone from the merchandise imported at dumping prices (Journal of Law 1997, no. 157, section 1028) raised considerable controversy among economists and stimulated a discussion on the principle of anti-dumping regulations coming into force as Poland was about to access the European Union. The paper discusses the Polish anti-dumping regulations stipulated in the above Law of December 11, 1997 that were binding until the accession day and the changes introduced with respect to anti-dumping regulations following Poland’s accession to the European Union.